2023
DOI: 10.1039/d2bm01496c
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies for tumor radiosensitization mediated by multifunctional gold-based nanomaterials

Abstract: Radiotherapy (RT) is one of the most effective and commonly used cancer treatments for malignant tumors. However, the existing radiosensitizers have a lot of side effects and poor efficacy, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 184 publications
0
7
0
Order By: Relevance
“…It consists of four phases: G1 phase, S phase, G2 phase, and M phase. Of the four stages, the G2/M phase is particularly sensitive to irradiation. , Therefore, biomaterials that can arrest cell cycle of tumor cells in the G2/M phase will enhance the radiosensitivity . The cell cycle progression was evaluated by flow cytometric determination of the DNA content after propidium iodide (PI) staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of four phases: G1 phase, S phase, G2 phase, and M phase. Of the four stages, the G2/M phase is particularly sensitive to irradiation. , Therefore, biomaterials that can arrest cell cycle of tumor cells in the G2/M phase will enhance the radiosensitivity . The cell cycle progression was evaluated by flow cytometric determination of the DNA content after propidium iodide (PI) staining.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 Therefore, biomaterials that can arrest cell cycle of tumor cells in the G2/M phase will enhance the radiosensitivity. 51 The cell cycle progression was evaluated by flow cytometric determination of the DNA content after propidium iodide (PI) staining. The number of cells in G0/ G1, S, and G2/M phases showed that the cells gradually accumulate in G2/M phase following exposure to X-ray radiation (Figure 4d and e Au/AgNDs along with the X-ray radiation cause a higher cell distribution in the G2/M phase and the arrest of the cell cycle mainly in the G2/M phase (Figure 4f).…”
Section: Radiotherapy Effect In Vitromentioning
confidence: 99%
“…101,102 Radiation therapy sensitization using NPs can improve the tumor's response to radiation by facilitating the production of reactive oxygen species, oxygen depletion, or glutathione depletion. 24,103,104 These approaches hold promise for improving ATC patients' quality of life and survival rates.…”
Section: Nanomaterials In Thyroid Cancer Treatmentmentioning
confidence: 99%
“…8,9 A promising direction for the treatment of malignant tumors is the use of complex nanomaterials, which include several components with special functions, potentially enhancing their therapeutic effect. [10][11][12][13][14][15] In particular, such complex nanomaterials are hybrid nanosystems containing photosensitizers, metal nanoparticles (NPs) and polymers.…”
Section: Introductionmentioning
confidence: 99%